Diversifikasi pengolahan ikan di Kabupaten Selayar - Halifah Pagarra; Hartati Hartati (Seminar Nasional Pengabdian Kepada Masyarakat, 2018)
Processed diversification of fishery products is oneof the technologies to increase the storability and longevity offishery products in the postharvest through processing andpreservation. The aims are to prevent decomposition of fish,especially during abundant production, and to increase theincome of fishermen or fish farmers. This activity aims toincrease knowledge and provide skills to High School teachersin Selayar Regency as a partner for the fulfillment ofnutritional sources of protein, increasing knowledge, skills,and income. The program was conducted in activelydemonstrative by involving partners fully from counseling todemonstrate making fish nuggets, otak-otak and fish meatballs.The results of this PKM program indicated that there has beenan increase in partner knowledge and skills regarding fishprocessing diversification technology as an appropriatetechnology to increase partner income levels as well as tofulfill the nutrition of animal protein sources for communities